Social prescribing - Drinkwater, Chris; Wildman, Josephine; Moffatt, Suzanne (BMJ (Online), 2019)
Non-medical interventions are increasingly being proposed to address wider determinants of health and to help patients improve health behaviours and better manage their conditions. 1 2 This is known as social prescribing. In England, the NHS Long Term Plan states that nearly one million people will qualify for referral to social prescribing schemes by 2023-24.3 Primary care networks, announced as part of the 2019 GP contract, will be funded to employ one social prescriber each from 2019.4 The social prescribing approach is also attracting interest in North America, 3 5 Australia, 6 and Scandinavia. 7 This clinical update outlines what social prescribing is, the evidence behind it, and offers some tips for embedding social prescribing within healthcare systems.